PEMBELAJARAN AKIDAH AKHLAK UNTUK MENUMBUHKAN KESABARAN DAN TAWAKAL SISWA MTS NU DARUL ANWAR MENGHADAPI TANTANGAN MORAL DIGITAL - Zulviyana, Silvia; In'ami, Moh (Al’ulum Jurnal Pendidikan Islam, 2025)
The problem in this study comes from the phenomenon of declining student character resilience in facing moral challenges in the digital era, such as a culture of showing off (flexing), cyberbullying, and instant mindset, which hinders the formation of patience and tawakal. This study aims to describe how the application of Akidah Akhlak learning in instilling the value of patience and tawakal in MTs NU Darul Anwar students. The method used is descriptive qualitative research with data collection techniques through observation, interviews, and documentation. The results showed that Akidah Akhlak learning was carried out through a contextual approach, the use of digital media in the form of inspirational videos, as well as religious habituation such as joint morning prayers and the delivery of exemplary stories. The strategy helps students understand the value of patience and tawakal, and apply it in facing social pressure and academic challenges. However, some students still show obstacles in value appreciation due to the influence of social media. In conclusion, Akidah Akhlak learning has a high urgency to continue to be developed adaptively so that it can become a moral and spiritual fortress for students in the face of rapid digitalization and shifting values.